The effect of growth medium and nutrient solution concentration on the growth of narcissus bulbs in soilless system (Damascus University Journal of agriculture sciences, 2023)
The research was conducted in the greenhouse of flowers in Abo-jarash farm- Agriculture college in Damascus university during the year of 2020. to study the effect of growing media and nutrient solution concentration on the growth of Narcissus bulb. The growth medium included 4 types, which are turb (control), turb: perlite(1:1, v:v) and turb: volcanic pumice (1:1, v:v), in addition to hydroponics with Deep flow technique(DFT) ; Each medium was irrigated with two concentrations of Hoagland and Amon nutrient solution (full and half concentration). The experiment was designed according to Randomized Complete Block Design (RCBD). Results indicated that the growth of narcissus bulbs (Number and length of leaves, length of roots) and its flowering standards (appearance date of the floral tube, date of flowers bloom and number of flowers on the floral tube) were improved significantly by using hydroponic system, followed by the treatment of turb: volcanic pumice and then turb: perlite. Where, the number of leaves increased by (87.98, 46.99, 34.43) % respectively in the treatments (hydroponic system, turb: volcanic pumice and turb: perlite) compared to the control (3.66 leaf/plant). The floral induction was after 62.41 days of cultivation in hydroponic system compared to the control (turb) (80.20 days).     For the number of bulblets, the results showed that the treatment turb: volcanic pumice (3.76 bulbs/plant) outperformed significantly all treatments, including the control (1.60 bulbs/plant), followed by the treatment turb: perlite which had significant differences with hydropnic system.Regarding the nutrient solution concentrations, no significant differences were recorded.
Keywords: Narcissus; growth media, concentration, soilless and nutrient solution